Karakterisasi Performa Genset Diesel 5 kW menggunakan Syngas Sekam Padi dengan Variasi Pembebanan - Restu Ferdinandsyah; Erwin Erwin; Slamet Wiyono (Fakultas Teknik Universitas Pancasila, 2022)
With the decrease in world oil reserves, energy savings have begun to be launched in almost all countries of the world. Indonesia has now become one of the crude oil importing countries, so efforts are needed to reduce dependence on oil and gas fuels. The sustainability of biomass gasification technology, especially in Indonesia, is highly guaranteed because of the abundant availability of biomass in Indonesia. The purpose of this study is to determine the performance of a 5 kW diesel generator against variations in loading with diesel fuel. The second is to know the performance of a 5 kW diesel generator against variations in loading with diesel fuel and rice husk syngas. Data collection on the performance characterization of the 5 Kw diesel generator set from syngas rice husks against variations in loading was carried out at the New Renewable Energy Engineering Laboratory. The loading carried out in this study was using a 5200 Watt halogen lamp. The power used in this study is only up to a maximum of 3200 Watt. The test result shows that the power generated by the generator is greater when using diesel fuel compared to using a mixture of diesel fuel with syngas. The value of the generator power for each loading variable increased when using low electrical load and decreasing when using high electrical load.